Supporting Tax Policy Change Through Accounting Discretion: Evidence from the 2012 Elections - Baloria, Vishal P.; Klassen, Kenneth J. (Management Science, 2018)
Some corporations attempt to lessen their tax burden through involvement in the legislative process. We identify firms that contributed to congressional candidates who favor reductions in the U.S. corporate statutory tax rate. This support created a temporary incentive to manage effective tax rates (ETRs) up. We document that these firms increased their reported effective tax rate in the two calendar quarters preceding the 2012 election relative to adjacent periods and other firms supporting candidates in the same election. We find that the variation in upward ETR management is correlated with firm-level proxies for potential reputational costs, capital markets costs, and long-run tax burdens. The variation in upward ETR management is also correlated with firm-candidate-level proxies for strength of relationships and competitiveness of election races. Our findings provide new evidence on accounting choices in support of corporate political activity and on the political cost hypothesis in the tax setting. The online appendix is available at https://doi.org/10.1287/mnsc.2017.2842 . This paper was accepted by Shivaram Rajgopal, accounting.